Risk factors for acquired multidrug-resistant tuberculosis - Barroso,Elizabeth Clara (2003)
Multidrug-resistant tuberculosis (MDR-TB) is a severe and feared problem, that is difficult to control and has shown a tendency to increase worldwide. OBJECTIVE: To analyze the risk factors for acquired MDR-TB. CASUISTIC AND METHODS: A retrospective population-based case-control study was conducted. A bacillus was considered multidrug-resistant whenever it was resistant at least to rifampin (RFP) + isoniazid (INH), and a case was considered as sensitive tuberculosis (TB) if it had undergone the first treatment during a similar period as the first treatment of an MDR-TB case, but was cured at the time of the interview. Case selection was made based on the list of Sensitivity Tests (ST) performed at the Central Public Health Laboratory of the State of Ceará, from 1990 through 1999. The Proportion Method was used to investigate resistance to the six antituberculosis drugs (isoniazid, rifampin, pyrazinamide, ethambutol, ethionamide, streptomycin) used as the standard treatment in Brazil. Controls were selected from the registry of the TB Control Program. Univariate and multivariate analysis were performed, with p < 0.05 considered significant. RESULTS: Out of the 1,500 STs performed during the studied period, 266 strains were multidrug-resistant; 153 patients were identified, 19 of which were excluded. The Group of Cases comprised 134 patients, and the Group of Controls comprised 185. Multivariate analysis helped to detect the following risk factors: lack of home sewer system, alcoholism + smoking, number of previous treatments, irregular treatment, and lung cavities. CONCLUSION: These five factors are important for the development of acquired MDR-TB, and an attempt to neutralize them might contribute to control TB.